Factors associated with parametrial involvement in patients with stage IB1 cervical cancer: Who is suitable for less radical surgery? - Seung-Ho Lee; Kyoung-Joo Cho; Mi-Hyang Ko; Hyun-Yee Cho; Kwang-Beom Lee; Soyi Lim (Korean Society of Obstetrics and Gynecology, 2018)
ObjectiveTo detect the possible clinicopathologic factors associated with parametrial involvement in patients with stage IB1 cervical cancer and to identify a cohort of patients who may benefit from less radical surgery.MethodsWe retrospectively reviewed 120 patients who underwent radical hysterectomy and pelvic lymphadenectomy as treatment for stage IB1 cervical cancer.ResultsOverall, 18 (15.0%) patients had parametrial tumor involvement. Tumor size larger than 2 cm, invasion depth greater than 1 cm, presence of lymphovascular space involvement (LVSI), corpus involvement, and positive lymph nodes were statistically associated with parametrial involvement. Multivariate analysis for other factors showed invasion depth >1 cm (P=0.029), and corpus involvement (P=0.022) were significantly associated with parametrial involvement. A subgroup with tumor size smaller than 2 cm showed no parametrial involvement, regardless of invasion depth or presence of LVSI.ConclusionTumor size smaller than 2 cm showed no parametrial involvement, regardless of invasion depth or presence of LVSI. Invasion depth >1 cm and corpus involvement were significantly associated with parametrial involvement in multivariate analysis. These finding may suggest that tumor size may a strong predictor of parametrial involvement in International Federation of Gynecology and Obstetrics stage IB1 cervical cancer, which can be used to select a subgroup population for less radical surgery.